2008
DOI: 10.1007/s00167-008-0512-3
|View full text |Cite
|
Sign up to set email alerts
|

Survival curve and factors related to drainage during the first 24 h after total knee arthroplasty

Abstract: Routine use of drains in total knee arthroplasty (TKA) is controversial. The aim of this study is to define the hourly risk of bleeding in the first 24 h following TKA using a survival study, to detect factors that might modify this risk, and establish a predictive model. In a retrospective study including 112 knees, patients with a coagulation disorder, platelet disease, or anticoagulation treatment were excluded. The risk factors studied included anesthesia score of the American society of anesthesiologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Therefore, drainage tube could be removed after 24 hours. Ares-Rodriguez et al 21 found that the drains used in TKA can be removed within the first 18 hours with a high degree of safety and low risk of persistent bleeding by using a survival study, which was further confirmed in the same study by Ares et al 22 In our study, there was no statistically significant difference in the volume of total blood loss and Hb levels preoperatively and on POD1, POD3 in the three groups, the decrease of Hb between preoperative and POD1, POD3 as well. No patient received a blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, drainage tube could be removed after 24 hours. Ares-Rodriguez et al 21 found that the drains used in TKA can be removed within the first 18 hours with a high degree of safety and low risk of persistent bleeding by using a survival study, which was further confirmed in the same study by Ares et al 22 In our study, there was no statistically significant difference in the volume of total blood loss and Hb levels preoperatively and on POD1, POD3 in the three groups, the decrease of Hb between preoperative and POD1, POD3 as well. No patient received a blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, bleeding survival curves were used to assess the time at which drainage ceases to be productive (0 mL) and 0 mL during the next hour. 17 Bleeding survival curves define the hourly risk of bleeding until it ceases.…”
Section: Methodsmentioning
confidence: 99%
“…No drainage was maintained for more than 24 hours due to the previous studies regarding the survival curve of bleeding, which concluded that the drains ceased being productive beyond 16 hours. 17 Patients were 24 hours in recovery room where the same nursing staff performed the measurements at 1, 12, and 24 hours. To avoid bleeding bias between cemented arthroplasties, noncemented, or hybrids, 18 only patients with a cemented arthroplasty were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, blood loss is a surgical complication that should be especially aware of in at-risk patients such as those with cardiovascular or anemic problems. Although blood loss itself has been described in other orthopedic procedures, such as knee replacement or hip fractures [ 9 - 11 ], to our knowledge, the present manuscript is the first to describe its impact within hip arthroscopy.…”
Section: Introductionmentioning
confidence: 98%
“…Our hypothesis was that significant blood loss occurred following hip arthroscopy, described as a loss in hemoglobin and hematocrit values, as it has been described in other orthopedic procedures [ 9 ].…”
Section: Introductionmentioning
confidence: 99%